Evaluating a single treatment planning beam model for multiple beam-matched linear accelerators - Koen, Liebner (University of the Free State, 2018)
The success of cancer treatment with radiation is highly dependent on the ability of the Treatment Planning System (TPS) to accurately calculate doses that would be delivered to the patient. The quality of TPS commissioning data, based on Linear Accelerator (Linac) measurements in water, largely determines the quality of the TPS beam model derived from this data. Modern treatment techniques such as Intensity Modulated Radiotherapy (IMRT) require highly accurate dosimetry equipment used for TPS commissioning. Once derived, the beam model should be verified with a range of tests other than commissioning procedures to test the beam model against Linac output. The study aims to investigate equivalences and differences between 5 Siemens ArtisteTM Linacs of similar output, referred to as beam-matched Linacs, and how a single TPS beam model (MonacoTM) can potentially be utilized for treatment planning for any of the Linacs. Generally, dosimeters used for TPS beam data collection differ largely from those used for post-modelling verification measurements. The study investigates the correlation between a high-resolution detector (microDiamond) typically used for collecting commissioning beam data and a post-modelling verification 2D array detector (Mapcheck2TM). Measurement resolution of Mapcheck2TM was increased to 1 mm by repetition measurements, manually stepping the device in-between the detector-less spaces and software developed to convert data to a readable format. Dose profiles from Mapcheck2TM, with increased measurement resolution, and microDiamond agreed well. This method was further used to accurately determine Multi-leaf Collimator (MLC) errors from a range of MLC stop positions across the radiation field for each Linac respectively. This allowed for quantitative comparisons that showed significant differences between the MLCs of the 5 Linacs. A new radiological calibration curve (containing software MLC offset values) to reduce MLC errors were proposed for each Linac respectively. Clinical IMRT treatment fields were measured with increased array resolution on each Linac and compared to dose calculations from the TPS. Gamma pass rates, from different measurement resolution and evaluation software, were above 95% for a criterion of 2%/2mm with confidence limits above 90%. Therefore, it is concluded that differences between Linacs in terms of IMRT treatment delivery were insignificant. Hence, an overall agreement in comparing the 5 beam-matched Linacs to IMRT dose calculation from a single TPS beam model respectively. Limitations of the planar IMRT QA evaluation method were discussed as well as the inability of this method to detect seemingly significant MLC errors.
Dissertation (M.Med.Sc. (Medical Physics))--University of the Free State, 2018
Keywords: 2D array; Diamond detector; Profiles; Spatial resolution; Beam-matching; MLC error; Treatment planning system; Intensity modulation radiation therapy